Facile technique to encapsulate phase change material in an amphiphilic polymeric matrix for thermal energy storage. (15th June 2021) - Pandey, Kalpana; Ali, Sana Fatima; Gupta, Sumit Kumar; Saikia, Pranaynil; Rakshit, Dibakar; Saha, Sampa
Highlights: Double emulsion technique was used to entrap n-Eicosane in amphiphilic polymer. Synthesize porous microcapsules possessing around 160 J/g latent heat. >95% encapsulation efficiency of n-Eicosan and 95% thermal energy storage capacity. Water dispersible, leak proof, highly durable and thermoregulation characteristics. Potential application area includes wall materials in energy saving buildings. Abstract: A facile fabrication technique of producing novel porous microcapsules encapsulating n-Eicosane as phase change material (PCM) with a random copolymer of poly (methyl methacrylate0.9 - co -2-hydroxyethyl methacrylate0.1 ) (poly(MMA0.9 - co -HEMA0.1 )) as shell material is being reported. The porous microparticles (particle size: 31.8 ± 9 µm; porosity: 30 ± 13%) with a hollow core (shell thickness: 1.60 ± 0.2 µm) were obtained by adopting a synthetic pathway of hot water assisted double emulsion (water/oil/water) system. Strikingly, the microcapsule system was found to entrap > 95% n-Eicosane, thus achieving significantly high thermal energy storage capability ( 95%). The porous microcapsules with a phase transition enthalpy of 160 J/g exhibited high phase transfer repeatability and long durability. The non-isothermal and isothermal DSC study further revealed the heat charging and discharging conditions for the microcapsules. Moreover, in contrast to neat hydrophobic PCM, the porous particles with partially hydrophilic shell (owing to polyHEMA unit) displayed better water dispersibility along with efficient thermal management characteristic as revealed by Infrared thermography. Thus, the microencapsulated phase change material in porous microcapsules can be a smart combination of good thermal energy storage function with wettability. Potentially such microcapsules may be exploited as thermal energy storage materials for space conditioning in buildings because of the suitable phase transition temperature (37 °C) displayed by the selected PCM (n-Eicosane). Our study comprehensively demonstrated water dispersible porous polymeric particles with significantly high thermal energy storage (>95%) performance that was not reported till date.